Про удосконалення методу розрахунку ресурсу циліндричних роликових підшипників - Гайдамака, Анатолій Володимирович; Скиба, Олександр Сергійович; Свіргун, Валентин Володимирович (НТУ "ХПІ", 2018)
Показано недоліки сучасного методу оцінки ресурсу динамічно навантажених циліндричних роликових підшипників, який не враховує в повній мірі особливості їх конструкції та умови експлуатації. Рівень дослідження механізму утворення перекосу кілець підшипників визнано недостатнім для побудови адекватної розрахункової моделі їх навантаження. Обґрунтовано напрям удосконалення розрахунку ресурсу циліндричних роликових підшипників за формулами ДержСТ 18855–94 шляхом уточнення методики визначення еквівалентного радіального навантаження.

The shortcomings of the modern method for estimating the life of dynamically loaded cylindrical roller bearings are shown, which does not fully take into account the features of their design and operating conditions. The level of investigation of the mechanism of the skewing of the bearing rings is recognized as insufficient for constructing an adequate calculation model of their loading. The direction of improvement of calculation of a life of cylindrical roller bearings is grounded on formulas GOST 18855–94 by specification of a technique of definition of an equivalent radial load. Improvement of the method for calculating the life of cylindrical roller bearings, which have the peculiarity of perceiving the axial load, requires solving tasks for determining the degree of influence of radial and axial loads on the distortions of rings and rollers, construction of models of contact interaction of parts under different types of distortion, clarification of the distribution of radial load on rollers and an equivalent radial load on the bearing.
On the improvement of the method of calculating the life of cylindrical roller bearings
Keywords: перекіс кілець; навантаження; метод розрахунку; skew of rings; load concentration; calculation method